The Effect Of The Teams Games Tournament (Tgt) Model Using Poster Media On Ipa Learning Outcomes In Class V Sd Negeri 12 Konda Village, Pombulaa Jaya, Konda District, Konsel - Titin Muliatin; Nikolaus Pasassung; Chairan Zibar L.Parisu (Prodi PGSD Unsultra, 2021)
This study aims to determine the effect of the Teams Games Tournament (TGT) learning model using poster media on students’ science learning outcomes. The research employed a quantitative approach with a quasi-experimental design. The findings revealed that the students’ average pretest score was 36.75, with a minimum score of 25 and a maximum of 50. Meanwhile, the posttest average score increased to 77.00, with a minimum of 70 and a maximum of 95. The results of the statistical analysis showed that the t-count (23.406) was greater than the t-table (1.6759), indicating a significant difference between the students’ learning outcomes before and after applying the Teams Games Tournament (TGT) model with poster media. The mean difference of 40.25 demonstrates a substantial improvement in learning outcomes. Based on these findings, it can be concluded that the Teams Games Tournament (TGT) learning model assisted by poster media has a significant positive effect on improving science learning achievement among fifth-grade elementary school students.